Time Delay Model of the Turbine Pressure Water Conduit: Application to the off-the-grid regime control. Issue 18 (2021) - Fišer, Jaromír; Zítek, Pavel; Kuchař, Michal; Peichl, Adam; Kučera, Milan; Kulík, Pavel; Vyhlídal, Tomáš
Abstract: The paper presents modeling the hydro-turbine governing system with delay in application to the turbo-machinery control. The delay originates from the wave phenomenon encountered in the pressure water conduit connected to the turbine. To facilitate the PID control tuning the turbine and conduit model is linearized and it results in linear time delay system referred to as the neutral system. Particularly, the disturbance rejection is achieved by the PID control response to varying power loads. Finally, the application example demonstrates the turbo-machinery control in the off-the-grid regime.